Suitability of Maize-legume intercrops with optimum row ratio in mid hills of eastern Himalaya, India - Choudhary, VK (SAARC Journal of Agriculture, 2015)
Maize (Zea mays L.) being a widely space crop were tried with different combinations of legumes cowpea (Vigna unguiculata L. Walp), frenchbean (Phaseolus vulgaris L.) and blackgram (Vigna mungo L.) as intercrops at different planting geometry to find out their suitability during 2009, 2010 and 2011 at eastern Himalayan, Arunachal Pradesh, India. Three experiments were carried out in sequence to identify suitable planting geometry to accommodate intercrops, screening best legume crops and subsequently best performed row ratio of maize and legume crops were intercropped in third experiment with 1:1, 1:2 and 1:5 row proportions. Sole maize gave the maximum grain yield with 4571.1 kg ha-1, whereas, stover yield was highest with maize-cowpea intercrop at 1:2 row ratios (8013.4 kg ha-1) and 57.1 kg ha-1 day-1 production efficiency followed by frenchbean and least with blackgram. Competition indices like land equivalent ratio (LER) was highest with 1:2 row ratio of maize-frenchbean (1.66), land equivalent coefficient (0.67). But, highest area time equivalent ratio (ATER) noticed with 1:2 row ratio of maizeblackgram (1.47). Relative crowding coefficient (K) and competition ratio were noticed higher with 1:2 row ratio of maize-cowpea, whereas, cowpea combinations has better crowding coefficient and blackgram combinations registered better competitiveness. Monetary advantage index (MAI) was 6433.2 with 1:2 row ratio of maize-blackgram followed by maize-cowpea and lowest with maize-frenchbean with the trend of 1:2>1:5>1:1 row ratios. DOI: http://dx.doi.org/10.3329/sja.v12i2.21916 SAARC J. Agri., 12(2): 52-62 (2014)